2021
DOI: 10.1007/s40120-021-00263-2
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical-Radiomics Nomogram for Functional Outcome Predictions in Ischemic Stroke

Abstract: Introduction: Stroke remains a leading cause of death and disability worldwide. Effective and prompt prognostic evaluation is vital for determining the appropriate management strategy. Radiomics is an emerging noninvasive method used to identify the quantitative imaging indicators for predicting important clinical outcomes. This study was conducted to investigate and validate a radiomics nomogram for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…Therefore, more objective and accurate analytical methods of [ 18 F]FDG PET/CT images were needed in neuroblastoma patients, especially in high-risk sub-group patients. Radiomics transforms medical images into quantitative indexes through high-throughput extraction by data-assessment algorithms for predicting important clinical outcomes [ 27 ]. After this research, the R_model showed a moderate power for predicting recurrence, with AUCs of 0.813 in the training set and 0.869 in the test set.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, more objective and accurate analytical methods of [ 18 F]FDG PET/CT images were needed in neuroblastoma patients, especially in high-risk sub-group patients. Radiomics transforms medical images into quantitative indexes through high-throughput extraction by data-assessment algorithms for predicting important clinical outcomes [ 27 ]. After this research, the R_model showed a moderate power for predicting recurrence, with AUCs of 0.813 in the training set and 0.869 in the test set.…”
Section: Discussionmentioning
confidence: 99%
“…The current results prove that with the radiomics technique, the essential temporal features of the impaired tissues could be captured. It is challenging to estimate clinical outcomes only by considering the radiomics features of lesions [ 29 ]. Multiple factors are associated with the functional outcome, as well as the features of the lesion itself.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is used to investigate tumor heterogeneity [ 19 , 20 ] and in clinical decision support systems to improve treatment decision making and accelerate advancements of clinical decision support systems in cancer medicine [ 21 , 22 , 23 , 24 , 25 , 26 ]. However, in the field of stroke, only a few studies have explored the role of radiomics in diagnosing ischemic stroke [ 27 ], penumbra-based prognosis assessment [ 28 ], and functional prediction [ 29 ]. For example, Tang et al [ 28 ] used a Lasso model to achieve multiclassification prediction with a maximum AUC of 0.77 by using radiomics features extracted from infarct and penumbra in CBF and ADC.…”
Section: Introductionmentioning
confidence: 99%
“…Some important risk factors previously reported such as coagulopathy were also included in multivariate regression. Collinearity was assessed via the variance inflation factor (VIF), and features with VIF values > 10 were excluded [ 24 ]. Variables for inclusion were carefully chosen to ensure the parsimony of the final model.…”
Section: Methodsmentioning
confidence: 99%